Scaffolding Academic Writing for First-Year EFL University Students: A PRISMA-Guided Systematic Review and Thematic Synthesis - Vike Aprilianin Marwintaria Saputri (Program Doktor Pendidikan FKIP Universitas Lampung, 2026)
Background: First-year EFL university students frequently encounter significant challenges in developing writing skills, necessitating effective instructional support. Although extensive research exists, gaps persist in understanding the impact of scaffolding strategies on writing abilities in higher education. Objective: This systematic review investigates scaffolding strategies for enhancing writing skills among first-year EFL students, focusing on (1) definitions and theoretical foundations, (2) strategies that improve writing ability, and (3) perceived challenges and benefits from both educators' and students' perspectives. Method: A systematic literature review was conducted in accordance with PRISMA guidelines across Scopus, ERIC, Web of Science, ProQuest, and Google Scholar (2019–2024). The search utilized keywords such as